LANGUAGE AS A SOCIAL PHENOMENON: A SOCIOLINGUISTIC ANALYSIS - Nusratullaeva Shokhista Sabirjon kizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article investigates language as a dynamic social phenomenon, rather than a linguistic internal faculty. By synthesizing foundational theories, from Saussure, Bakhtin, Labov and Hymes, it explores how speech patterns reflect class structures, power dynamics, and communicative competence. Ultimately, the paper asserts that every linguistic act is a social performance that both reflects and actively constructs the shared social reality of a community.